Strategi Meningkatkan Konsentrasi Dan Regulasi Emosi Siswa Melalui Pendekatan Neurosains - Zilfania Qathrun Nada; Rovina Sellanie; Afnan Awwaluddin (STAI AL-AMIN, 2025)
This study aims to examine the effectiveness of the Brain Gym strategy in improving concentration and emotional regulation among elementary school students. The background of this research stems from students’ difficulties in maintaining focus and managing emotions, which negatively affect their academic performance. This study employs a quantitative approach using an experimental method with a one-group pretest-posttest design. The population consisted of all third-grade students at MI Nururrahmah in the 2024/2025 academic year, with a sample of 15 students selected through simple random sampling. The research instruments included a concentration test in the form of basic arithmetic problems and an emotional regulation questionnaire using a Likert scale. Data were analyzed using descriptive and inferential statistics, including normality tests (Shapiro-Wilk), homogeneity tests (Levene’s test), paired sample t-tests, and effect size calculations (Cohen’s d). The results showed an increase in the average concentration score from 5.4 to 6.8 and in emotional regulation from 2.04 to 2.44 after the intervention. The paired sample t-test indicated a significant difference (Sig. < 0.001), while Cohen’s d revealed a moderate effect size for both variables (0.49 for concentration and 0.41 for emotional regulation). Therefore, it can be concluded that Brain Gym is effective in enhancing students’ concentration and emotional regulation in a primary school setting.